Konsep Pendidik dan Peserta Didik Dalam Perspektif Al-Qur’an - Almaydza Pratama Abnisa (STAI Asy-Syukriyyah, 2017)
Understanding educators or teachers are limited as one individual figure who is in front of the class. In a broad sense is a person who has the duty of responsibility to educate learners in developing their personality, both take place in school or outside school. According UUSPN 1989, teachers include educational staff, especially educators who are tasked with guiding, teaching and training students. In modern educational terminology, educators are called people who give lessons to their students by holding one discipline in school. Generally the educator is the person who has the responsibility to educate. While in particular, educators in the perspective of Islamic education are those who are responsible for the development of learners by seeking the development of all potential learners, both affective potential, cognitive, and psychomotor in accordance with the values of Islamic religious teachings. Students themselves in Islamic education are individuals who are growing and developing, both physically, psychologically social, and religious in the world through the life and the hereafter. Imam Ghazali points out that the primary task of the educator is to perfect, cleanse, purify, and bring the human heart to taqarrub ila Allah.